"Чорні лебеді" Української революції: (не)ймовірні випадки західноукраїнської державності - Монолатій, І. (Український історичний журнал, 2020)
Мета статті полягає в дослідженні маловивчених і дискусійних проблем Української
революції, зокрема особливостей становлення й розвитку західноукраїнської державності в
1918–1919 рр., а також окремих питань політичної історії Західноукраїнської Народної Республіки 1918–1923 рр., ґрунтуючись на теорії «чорного лебедя» Н.Н.Талеба. Методологія дослідження
спирається на принципи історизму, етнічної політології, системності, науковості, міждисциплінарності. Використано такі загальноісторичні методи: історіографічний, історико-генетичний і термінологічний аналіз, компаративний, типологічний. Автор дотримується методології інституціоналізації політичних áкторів в умовах політизації етнічностей. Наукова новизна. Обґрунтовано три
дослідницьких гіпотези, пов’язані з подіями на Галичині 1918–1919 рр.: Листопадовий зрив – як
«чорний лебідь» західноукраїнської державності; проголошення Українською Національною
Радою об’єднання ЗУНР з Українською Народною Республікою – як приклад «чорного лебедя»,
оскільки практична (не)реалізація задуму мала серйозніші наслідки, ніж здавалося сучасникам;
проголошення диктатури Є.Петрушевича 9 червня 1919 р. (ще один «чорний лебідь»), що призвело до повернення до правової моделі ЗУНР і слідування в напрямку самостійної «Галицької Держави». Висновки. Листопадовий зрив 31 жовтня – 1 листопада 1918 р. засвідчує не лише
Талебовий перехід від середньостану (Габсбурзької монархії – тиранії колективного) до крайньостану (ЗУНР – тиранії випадкового), а його «чорного лебедя» – події екстремального характеру,
котра мала епохальні наслідки для реґіону. Листопадовий зрив став «чорним лебедем» не для
тогочасних галицьких українців (хоча й почасти), а для «чужих» – насамперед поляків та євреїв
на Галичині. З іншого боку, ця подія (як «чорний лебідь») спровокувала нову (після Першої світової) війну – спочатку за Львів, а вже потім і за Галичину. Тому ця обставина лише загострює проблему «чорного лебедя» як (не)ймовірного випадку західноукраїнської державності 1918–1919 рр. ЗУНР як крайньостан уже після Листопадового зриву потерпала від «чорного лебедя»; досвід
минулого не допоміг реґіональним політичним áкторам передбачити майбутнє (Галичини, ЗУНР);
тиранія випадкового (емоційно забарвлене рішення УНРади від 3 січня 1919 р.) трапилася знову
й переможець (УНРада) отримав усе, чого домагався (приєднання до УНР); історія почала знову
«стрибати» – уже після 22 січня 1919 р. Однак, зважаючи на Талебові міркування, другий «чорний
лебідь» – це, скоріш за все, «недо-чорний», «сірий лебідь». Його з’яву передбачали найперше
зовнішні, а вже потім внутрішні політичні áктори, починаючи з грудня 1918 р.: вони були готові до
його появи (що й відбулося 3 січня 1919 р.), а відповідним інструментарієм став «передвступний
договір», підписаний у Фастові. Акт установлення диктатури від 9 червня 1919 р., хоча й не безпосередньо (однак за наявності інших складових), певною мірою призвів до зміни статусу Галичини
на геополітичній шахівниці тогочасної Європи, що його увиразнив цілий «каскад» подій: 1) рішення Найвищої ради Паризької мирної конференції від 25 червня 1919 р. про дозвіл Польщі зайняти Галичину; 2) Варшавський договір 1920 р. (Пілсудського – Петлюри), згідно з яким до Польщі мала відійти і Східна Галичина; 3) Ризький договір 1921 р., що, фактично, анулював Варшавський,
а УСРР відмовилася від претензій на Східну Галичину, передавши її ІІ Речіпосполитій; 4) рішення
Ради послів держав Антанти від 15 березня 1923 р. про визнання суверенітету Польщі, у тому числі й над Східною Галичиною. The purpose of the study are understudied and disputable aspects of the Ukrainian
Revolution, mainly on how Western Ukrainian statehood was established and developed in 1918–
1919, as well as some specific issues of the political history of Western Ukrainian People’s Republic
(WUPR) in 1918–1923, building up on the theory of Black Swans developed by Nassim Nicholas
Taleb, a Lebanese-American mathematician. The research methodology is based on the principles
of historicism, ethnical politology, systemicity, science, interdisciplinarity. The following general
historiographical methods are used: historiographical analysis, historical-genetic, terminological
analysis, comparative, typological. The author adheres to the methodology of institutionalization
of political actors in the context of politicization of ethnicities. The scientific novelty. The first
hypothesis studies the November Action as the Black Swan of Western Ukrainian statehood.
The second deals with the events of 3 January 1919 when the Ukrainian National Rada (Council)
approved the union of WUPR and Ukrainian People’s Republic (UPR) that in the author’s opinion is
an example of the Black Swan because its (non)implementation had far more grave consequences
than its contemporaries thought it would. The third theory analyses another Black Swan, which is
the nomination of Ye.Petrushevych as a dictator on 9 June 1919 that led to the return to WUPR legal
framework and the pursuit of the independent “Halychyna State”. Conclusions. The first hypothesis
demonstrates that the November Action of 31 October – 1 November 1918 testifies not only to Taleb’s
transition from Mediocristan that is the Habsburg Empire, a tyranny of the collective, to Extremistan
represented by WUPR, a tyranny of the accidental, but also to the Black Swan event that had epochal
consequences for the studied region. The author is certain, the November Action became the Black
Swan not only for Halychyna Ukrainians (to some extent, though) but also for “strangers”, first of
all for Poles and Jews residing in Halychyna. On the other hand, the November Action, as the Black
Swan, sparked a new warfare (after World War I) first for Lviv and then for Halychyna. Therefore, this
situation just aggravates the Black Swan problem as an (im)probable event of Western Ukrainian
statehood in 1918–1919. The second hypothesis indicates that WUPR being Extremistan after the
November Action (1 November 1918) suffered from the Black Swan. Experience of the past did not
help regional political actors to foresee the future including the one for Halychyna and for WUPR.
The tyranny of the accidental that was the emotionally tinged decision of the Ukrainian National
Rada on 3 January 1919, happened again, and the winner, the Ukrainian National Rada, took all
it aspired to, i.e. joining the Ukrainian National Rada. The history started “jumping” again – this
time after 22 January 1919. However, keeping Taleb’s contemplations in mind, the second Black
Swan is more likely to be nearly-Black or Grey given the fact that its occurrence was foreseen
first by external and then by internal political actors after December 1918. They were ready to
that happening which eventually took place on 3 January 1919, and the Preliminary Agreement
being signed in Fastiv worked as a suitable tool. The third hypothesis proves, the introduction of
Dictatorship on 9 June 1919, indirectly though, in a certain way led to the change of Halychyna’s
status on the geo-political chessboard of Europe. This new status got embodied through a “cascade”
of events: 1) the decision of the Supreme Council at the Paris Peace Conference on 25 June 1919
to allow Poland to take over Halychyna; 2) the Treaty of Warsaw (Piłsudski – Petliura Agreement)
of 1920 under which Eastern Halychyna, among other lands, was ceded to Poland; 3) the Treaty of
Riga of 1921 which de facto abrogated the Treaty of Warsaw, whereas UkSSR renounced its claims
to Eastern Halychyna by handing it over to II Rzeczpospolita; 4) by its decision of 15 March 1923, the
Conference of Ambassadors of the great powers of the Entente recognized the sovereignty of Poland
with Eastern Halychyna being part of its territory. In the conclusions author emphasizes that under
Taleb’s theory, the Black Swans of the Ukrainian revolution scaled down to Western Ukraine could
be assigned to the respective quadrants: the first Black Swan (the November Action) to the Fourth
Quadrant of the positive Black Swan, the third Swan (Dictatorship of the Western Province of UPR)
also to the Fourth Quadrant but of the negative Back Swan. Though, the second Black Swan or the
first and the only Grey Swan (Ukrainian National Rada’s decision on the union) is most likely to be in
the Third Quadrant which implies simple payoffs, i.e. the probability of this Swan had no impact on
the final result (22 January 1919). Hence, they are only the November Action and the Dictatorship
that fit in the Fourth Quadrant of the Black Swan domain.